A semi-synthetic neolignan derivative from dihydrodieugenol B selectively affects the bioenergetic system of Leishmania infantum and inhibits cell division - Amaral, M; de Sousa, F; Silva, T; Junior, A; Taniwaki, N; Johns, D; Lago, J; Anderson, E; Tempone, A (Springer Nature, 2019)
Leishmaniasis is a neglected disease that affects more than 12 million people, with a limited therapy. Plant-derived natural products represent a useful source of anti-protozoan prototypes. In this work, four derivatives were prepared from neolignans isolated from the Brazilian plant Nectandra leucantha, and their effects against intracellular amastigotes of Leishmania (L.) infantum evaluated in vitro. IC50 values between 6 and 35 µM were observed and in silico predictions suggested good oral bioavailability, no PAINS similarities, and ADMET risks typical of lipophilic compounds. The most selective (SI > 32) compound was chosen for lethal action and immunomodulatory studies. This compound caused a transient depolarization of the plasma membrane potential and induced an imbalance of intracellular Ca2+, possibly resulting in a mitochondrial impairment and leading to a strong depolarization of the membrane potential and decrease of ATP levels. The derivative also interfered with the cell cycle of Leishmania, inducing a programmed cell death-like mechanism and affecting DNA replication. Further immunomodulatory studies demonstrated that the compound eliminates amastigotes via an independent activation of the host cell, with decrease levels of IL-10, TNF and MCP-1. Additionally, this derivative caused no hemolytic effects in murine erythrocytes and could be considered promising for future lead studies.